Hannah Arendt: the last interview : and other conversations - Arendt, Hannah 1906-1975 (Melville House Publ, 2013)
"A unique selection of the most significant interviews given by Hannah Arendt, including the last she gave before her death in 1975. Some are published here in English for the first time. Arendt was one of the most important thinkers of her time, famous for her idea of "the banality of evil" which continues to provoke debate. This collection provides new and startling insight into Arendt's thoughts about Watergate and the nature of American politics, about totalitarianism and history, and her own experiences as an emigre. Hannah Arendt: The Last Interview and Other Conversations is an extraordinary portrait of one of the twentieth century's boldest and most original thinkers. As well as Arendt's last interview with French journalist Roger Errera, the volume features an important interview from the early 60s with German journalist Gunter Gaus, in which the two discuss Arendt's childhood and her escape from Europe, and a conversation with acclaimed historian of the Nazi period, Joachim Fest, as well as other exchanges. These interviews show Arendt in vigorous intellectual form, taking up the issues of her day with energy and wit. She offers comments on the nature of American politics, on Watergate and the Pentagon Papers, on Israel; remembers her youth and her early experience of anti-Semitism, and then the swift rise of the Hitler; debates questions of state power and discusses her own processes of thinking and writing. Hers is an intelligence that never rests, that demands always of her interlocutors, and her readers, that they think critically. As she puts it in her last interview, just six months before her death at the age of 69, "there are no dangerous thoughts, for the simple reason that thinking itself is such a dangerous enterprise.""--